What cardiologists need to know about cardiovascular magnetic resonance (CMR) - Bridgman, J. Cameron; Srinivasan, Govind; Selvanayagam, Joseph B. (SA Heart Journal, 2017)
Cardiovascular Magnetic Resonance (CMR) is increasingly used in the evaluation of patients with cardiac and aortic disease. The ability to characterise myocardial tissue, function and anatomy (in any plane) without any exposure to ionising radiation are the main advantages over other imaging modalities used in cardiology. In this article we discuss the principles underlying the imaging technique, safety issues, indications and strengths of CMR. It aims to provide a concise, practical overview for the general cardiologist.